2018
DOI: 10.1016/j.marpolbul.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of seaweed cultivation on ecosystem services - a case study from the west coast of Sweden

Abstract: Seaweed cultivation attracts growing interest and sustainability assessments from various perspectives are needed. The paper presents a holistic qualitative assessment of ecosystem services affected by seaweed cultivation on the Swedish west coast. Results suggest that supporting, regulating and provisioning services are mainly positively or non-affected while some of the cultural services are likely negatively affected. The analysis opens for a discussion on the framing of seaweed cultivation - is it a way of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
104
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 55 publications
0
104
0
2
Order By: Relevance
“…In Sweden the efforts are mainly concentrated in the west coast, where the salinity is >20. The "Seafarm project" -involving five Swedish universities -was launched in 2014 to foster research around a cultivated Saccharina latissima biorefinery supply-chain, which resulted in the establishment of a first experimental seaweed farm in the Koster archipelago in Skagerrak (Hasselstrom et al 2018). A number of studies conducted in Denmark also estimated the regional potential of cultivated kelps or Ulva lactuca for production of biogas, bioethanol, biobutanol and more advanced biorefineries (Bruhn et al 2011, Alvarado-Morales et al 2013, Hou et al 2015.…”
Section: Seaweed Aquaculturementioning
confidence: 99%
See 3 more Smart Citations
“…In Sweden the efforts are mainly concentrated in the west coast, where the salinity is >20. The "Seafarm project" -involving five Swedish universities -was launched in 2014 to foster research around a cultivated Saccharina latissima biorefinery supply-chain, which resulted in the establishment of a first experimental seaweed farm in the Koster archipelago in Skagerrak (Hasselstrom et al 2018). A number of studies conducted in Denmark also estimated the regional potential of cultivated kelps or Ulva lactuca for production of biogas, bioethanol, biobutanol and more advanced biorefineries (Bruhn et al 2011, Alvarado-Morales et al 2013, Hou et al 2015.…”
Section: Seaweed Aquaculturementioning
confidence: 99%
“…In addition, exploitation of the bio-mitigation capacity of cultivated seaweed in the framework of integrated multitrophic aquaculture (IMTA), or as a compensation for increased animal aquaculture is coming more and more into focus (e.g. Sandow 2007, Holdt and Edwards 2014, Marinho et al 2015a, Hasselstrom et al 2018, Buck and Grote 2019. For example, seaweed cultivation is explicitly mentioned in Denmark's National Strategic Plan for the Development of Sustainable Aquaculture 2014-2020 as a compensation measure to bioremediate waste nutrients of fish and shellfish aquaculture (Ministeriet for Fødevarer Landbrug og Fiskeri 2016) and the Danish Government is currently seeking to facilitate investment in the creation of zones with integrated aquaculture (Ferdouse et al 2018).…”
Section: Seaweed Aquaculturementioning
confidence: 99%
See 2 more Smart Citations
“…It does not need land, fresh water, fertilisers, or pest-insect-or fungicides to grow, and the biomass can be used for many purposes, such as food 2 , feed 3 , materials 4 , biofuels 5 , or as gelling or stabilising substance in a range of applications 6 . Additionally, seaweed farming provides positive externalities in terms of ecosystem services such as generating habitats for fish and crayfish species and sequestering nutrients 7 . In a recent study, it is suggested that phosphorus uptake from large-scale seaweed cultivation in China can significantly contribute to mitigating coastal eutrophication 8 , and it has also been suggested as a potential carbon sink 9,10 .…”
mentioning
confidence: 99%